The Frequency of Fast-Food Consumption and the Habit of Using Gadgets and Playing Games as Risk Factors for Childhood Obesity - Zunnahri, Salsabila Qurrotul Aini; Sulistiawati, Sulistiawati; Athiyyah, Alpha Fardah; Fatmaningrum, Widati; Adiwinoto, Ronald Pratama (Universitas Airlangga, 2025)
Highlights: No relationship between the frequency of fast-food consumption as a risk factor for obesity in elementary school children. This result was based on interviews with students of Rangkah VII Elementary School during their daily life activities and their tendencies. No relationship between the habit of playing gadgets and games as a risk factor for obesity in elementary school children. This result was based on interviews with students of Rangkah VII Elementary School during their daily life activities and their tendencies. Abstract Introduction: Obesity is defined as the result of excessive fat accumulation caused by an energy imbalance, and it poses significant health risks. The contributing factors to be considered in this instance are the frequent consumption of fast food and reduced physical activity, which result from the increased use of gadgets and games. This study aimed to investigate the correlation between the aforementioned factors and the prevalence of obesity among elementary school children. Methods: The heights and weights of 112 participants were measured to calculate their body mass index (BMI). The respondents were interviewed directly about their fast-food consumption habits over a one-week period and their daily use of gadgets and games. This study employed bivariate analysis to examine the relationships between variables in a sample, using the Chi-Square test with odds ratio determination, a 95% confidence interval, and a significance level of 0.05, as implemented in the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 29. Results: The chi-square test showed p>0.05, indicating no significant relationship between fast-food consumption or gadget use and obesity in elementary school children. Conclusion: There was no association between the frequency of fast-food consumption and the habit of playing gadgets and games as a risk factor for obesity in elementary school children.